2017
DOI: 10.4314/jab.v114i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening and antibacterial investigations of crude methanol extracts of <i>Senna didymobotrya</i> (Fresen.) H. S. Irwin & Barneby

Abstract: Objective: Senna didymobotrya (African senna, African wild sensitive plant, peanut butter cassia, peanut butter tree, popcorn cassia, popcorn senna or wild senna) is native to East Africa and is widely used as a medicinal plant among many communities in Kenya. The objective of this research was to evaluate the presence of phytochemicals present in the different plant parts and their antibacterial activity. Methodology and results: Leaves, flowers, stem bark, immature pods and root barks were collected from Sia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 22 publications
(22 reference statements)
0
16
0
Order By: Relevance
“…Jeruto et al [76] found that its stem and root extracts had high efficiencies in inhibiting fungus growth while Jeruto et al [77] [72] to the entire study area shows new species habitat areas within unsampled protected areas (Fig 1) hence proving the usefulness of SDMs. Threats posed by alien plants invasion in high conservation areas is usually significant [74].…”
Section: Discussionmentioning
confidence: 91%
“…Jeruto et al [76] found that its stem and root extracts had high efficiencies in inhibiting fungus growth while Jeruto et al [77] [72] to the entire study area shows new species habitat areas within unsampled protected areas (Fig 1) hence proving the usefulness of SDMs. Threats posed by alien plants invasion in high conservation areas is usually significant [74].…”
Section: Discussionmentioning
confidence: 91%
“…The difference was attributed to the application of the plant extract on the treated tomatoes. The antifungal activity of the extract is attributed to the presence of phytochemical compounds in the extract and their antifungal capabilities [7]. The extract not only inhibits the growth of fungi but also bacteria [11] thus a total viable count becomes relevant [14].…”
Section: Resultsmentioning
confidence: 99%
“…Senna didymobotrya is a medicinal plant ( Fig. 1) growing naturally in East Africa and is commonly used medicinally to treat bacterial and fungal infections among African communities [7]. It contains various phytochemicals that include alkaloids, terpenoids, anthraquinones, tannins, saponins, phenols and flavonoids which have antimicrobial capabilities [8].…”
Section: Introductionmentioning
confidence: 99%
“…The extracts were evaluated qualitatively for the presence of flavanoids, tannins, saponins, alkaloids, glycosides, cardiac glycosides, volatile oils and steroids Jeruto et al [14]; Vijaya et al [15] Semenya et al [16].…”
Section: Phytochemical Analysismentioning
confidence: 99%